The Implementation of Interactive E-Books in the TEFA Learning Model to Improve Students’ Cognitive Abilities - Ain, Faridah Khurotul; Qudus, Nur (Journal of Vocational and Career Education, 2025)
Vocational High Schools (SMK) play a crucial role in preparing their graduates to work in both industry and the professional workforce. The learning process is expected to be carried out optimally by teachers to ensure quality education. Based on observations at SMKS Kerabat Kita Bumiayu, it was found that the TEFA learning model being developed has not yet been supported with adequate teaching materials that facilitate students’ cognitive understanding in the classroom. This highlights the need for integrating technology in the form of interactive e-books to support the learning process of vocational students. The objective of this study is to analyze the feasibility, effectiveness, and practicality of interactive e-books in learning, as well as to examine whether their implementation can improve students’ cognitive learning outcomes The research design employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as the development framework. Data analysis in this study assessed the feasibility, practicality, and effectiveness of the interactive e-book. The results of media expert validation indicated an average score of 4.54 (highly feasible), while the subject matter expert validation yielded an average score of 4.50 (highly possible). The practicality test conducted by users achieved an average score of 99.5% (highly practical). The effectiveness test, carried out through pretest and posttest, significantly improved students’ cognitive scores. This study concludes that the developed interactive e-book is highly feasible, practical, effective, and significantly enhances students’ mental abilities, particularly in the elements of basic accounting and banking principles and concepts within the subject of Fundamentals of the Accounting Program